CONTRIBUCION AL CONOCIMIENTO DE LOS MURCIELAGOS III - VILLA RAMIREZ, BERNARDO; MARTINEZ, LIBORIO (Universidad Nacional Autónoma de Mexico, CD MEXICO, DF, MEX, 1941)
Feeding upon scorpions (Centruroides [female][female]) the bugs reach the 1st moult in a good condition; they can not pass the moult unless fed on guinea-pigs[long dash]Between moults and number of meals there is a close relation, but between the number
ANS INST BIOL
Keywords: CONTRIBUCION, CONOCIMIENTO, MURCIELAGOS III; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; MAMIFEROS